Innovative aerosol technology using lemon peel-derived carbon dots for improving shelf life of beef - Ehsan Semsari; Hossein Tajik; Rahim Molaei; Mehran Moradi (Applied Food Research)
Carbon dots (C-dots) have gained significant attention for their applications in the food industry due to their unique optical and biological properties. In this study, C-dots were synthesized from lemon peel using a hydrothermal method and their effects on beef fillets were investigated via aerosolization. Particle size analysis revealed an average C-dot size of 7.55 nm, and transmission electron microscopy confirmed the spherical shape of the dots. The radical scavenging assay indicated an antioxidant capacity with a 50 % scavenging effect of 0.66 mg/mL. Low cytotoxicity on L929 mouse fibroblasts was observed at concentrations below 0.5 mg/mL, suggesting good biocompatibility. Beef fillets were treated with C-dots at two concentrations (5 and 10 mg/mL) by aerosolization. Quality indicators (pH, total volatile basic nitrogen, thiobarbituric acid value, psychrophilic and mesophilic bacterial counts, and sensory evaluation) were measured during 15 days of refrigerated storage and showed concentration-dependent control of microbial growth and inhibition of oxidation in meat samples with 10 mg/mL proving more effective than 5 mg/mL. Both concentrations delayed spoilage by at least three days. Despite minimal color changes, sensory analysis revealed improved odor scores (characterized by smoky notes) in C-dot-treated samples. This improvement, likely due to the prevention of off-odors, led to higher overall acceptability ratings compared with the control group. These findings suggest that C-dots synthesized from lemon peel could extend the shelf life of beef fillets, and aerosolization of C-dots offers a method to reduce the amount of C-dots required while maintaining or improving the quality of beef fillets during storage.